The Effects of Inflectional Variation on Fast Mapping of Verbs in English and Spanish - Bedore, Lisa M; Leonard, Laurence B (Journal of speech, language, and hearing research, 2000)
To use morphological cues for syntactic bootstrapping, children must recognize that inflectionally varying words (e.g., pushes, pushed ) are instances of the same word. Children who are exposed to languages with richer inflectional morphologies than English, such as Spanish, encounter instances of inflectional variation more often. Thus they may learn to recognize inflectionally varying words as instances of the same word at an earlier age than do learners of English. English- and Spanish-learning 3-year olds were taught novel verbs in a fast mapping task under two conditions: no-inflectional variation in which inflections did not vary between exposure and testing (e.g., neps, neps ) and inflectional variation in which inflections alternated between exposure and testing (e.g., neps, nepped ). Children’s scores were significantly higher in the no-variation condition than in the variation condition. There were no significant differences between the performance of the language groups. These findings suggest that even children acquiring languages with relatively rich verbal inflection paradigms may not be able to consistently parse stems and inflections to associate inflectionally varying forms.